2007
DOI: 10.1007/s00417-007-0699-x
|View full text |Cite
|
Sign up to set email alerts
|

fs-Laser induced elasticity changes to improve presbyopic lens accommodation

Abstract: Generating particular cutting patterns inside lens tissue can increase the deformation-ability of the crystalline lens. Thus, it might be one possible way to treat presbyopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 20 publications
1
45
0
2
Order By: Relevance
“…Previous research by Hollman et al (2003) ultrasonically observed an increase in human lens deformation by radial stretching after LIOB treatment over a large grid using the same Nd:glass laser as the present study. Finally, Ripken et al (2005) have created microcuts using a femtosecond Ti:Sapphire laser within porcine lenses and measured an increased deformability during lens spinning measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research by Hollman et al (2003) ultrasonically observed an increase in human lens deformation by radial stretching after LIOB treatment over a large grid using the same Nd:glass laser as the present study. Finally, Ripken et al (2005) have created microcuts using a femtosecond Ti:Sapphire laser within porcine lenses and measured an increased deformability during lens spinning measurements.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of different treatments under development, including scleral implants, corneal surgeries, pharmacological interventions to soften the lens, artificial intraocular lens implants, and laser surgery of the lens [74]. Lenticular surgery aims to restore flexibility by breaking the hardened-tissue structures and creating gliding planes of tissue [75]. Previous surgical attempts with nanosecond or picosecond lasers left behind residual gas bubbles, but femtosecond laser ablation of the lens yields lesions with bubbles that resolve with time [76].…”
Section: Presbyopiamentioning
confidence: 99%
“…In further investigations of the treatment of enucleated porcine and human autopsy lenses, Ripken et al [10] showed that cutting a 3D pattern inside the lens tissue with femtosecond laser pulses can increase the mechanical flexibility of the lens (Figure 1). Moreover, the flexibility of the lens increased depending on the particular cutting pattern [10,11].…”
Section: Introductionmentioning
confidence: 97%